Influence of Bio-Diesel and Ethanol on the Diesel Engine Process Chain Investigated by Optical Measurement Techniques - Rieß, Sebastian; Klima, Tobias C.; Wensing, Michael; Braeuer, Andreas (ILASS – Europe 2016, 27th Annual Conference on Liquid Atomization and Spray Systems, 4-7 September 2016, Brighton, UK, 2016)
The influence of bio-fuel components Ethanol and RME on injection, fuel propagation, phase transition, mixture formation, and auto-ignition is investigated. Different measurement techniques are therefore applied in a permanently scavenged high temperature/high pressure injection and combustion vessel: Injected mass and mass flow rates are measured using a HDA injection quantity and rate measuring unit. Liquid fuel penetration is investigated by means of Mie scattering technique. For analyzation of the mixture formation a Raman spectroscopy measurement setup is realized. The ignition delay is investigated statistically analysing the temporal occurrence of the chemical luminescence signal of OH*. It is shown that mixture formation is independent of temperature and physical properties of the fuel components as the spray can be regarded as gas flow with the main component nitrogen. Local mixture quality is a consequence of the molecular structure of the fuel. Ignition and combustion depend on chemical properties of the blend components.<br